2010
DOI: 10.1016/j.regsciurbeco.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Thick market externalities in a spatial model

Abstract: It is natural to think of thick market externalities as spatial phenomena. When agents are in close physical proximity, potential trading partners are more numerous and less costly to reach. Counteracting such agglomeration benefits is the dispersion force due to land being an essential input in production. The distribution of economic activities over space is an outcome of how decisions on location, land demand, and the search strategy of agents interact in spatial equilibrium. More desirable locations are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A body of research has studied the relationship between city sizes and wages and has shown that wages are higher in larger cities (for example, Glaeser 2008;Baum-Snow and Pavan 2013). Such benefits of density come from agglomeration economies (Glaeser and Maré 2001;Rosenthal and Strange 2008;Tse 2010;Davis and Dingel 2019). For instance, denser labor markets facilitate the matching of workers and employers and the exchange of productive ideas.…”
Section: Relation To the Literaturementioning
confidence: 99%
“…A body of research has studied the relationship between city sizes and wages and has shown that wages are higher in larger cities (for example, Glaeser 2008;Baum-Snow and Pavan 2013). Such benefits of density come from agglomeration economies (Glaeser and Maré 2001;Rosenthal and Strange 2008;Tse 2010;Davis and Dingel 2019). For instance, denser labor markets facilitate the matching of workers and employers and the exchange of productive ideas.…”
Section: Relation To the Literaturementioning
confidence: 99%
“… This is proved more formally in Tse (2010) in a setting that does not allow for agents choosing to become middlemen. If the matching rate is not straightly proportional to the mass of agents residing in the search area, the optimal search area of an agent can stop short of reaching all other agents with which a trade can profitably be carried out. …”
mentioning
confidence: 97%
“…In Beckmann (1976), where each household maximizes utility over land and nonland consumption subject to paying a traveling expense that is proportional to the average distance between the given household and the rest of the city’s population, the equilibrium distribution is symmetric and unimodal around the city center. In Tse (2010), I generalize the analysis to where an agent may choose to just travel to meet a subset of agents in the regional economy; the resulting distribution remains symmetric and unimodal around the center.…”
mentioning
confidence: 99%
See 2 more Smart Citations